1960
DOI: 10.2134/agronj1960.00021962005200100014x
|View full text |Cite
|
Sign up to set email alerts
|

Root Development of Coastal Bermudagrass with High Nitrogen Fertilization1

Abstract: Synopsis Coastal bermudagrass root weight per acre remained at a high level while nitrogen content of the roots, and organic matter content of the soil increased slightly as fertilizer nitrogen rates increased from 0 to 1600 pounds per acre. Hay yields were greatly increased with the same treatments resulting in an 8‐fold change in the root‐top ratio. Stands and yields have been maintained over a 6‐year period with nitrogen treatments ranging from 0 to 1600 pounds per acre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Production of Underground Plant Material.-Investigations of root production and distribution as influenced by fertilization, indicated varied and conflicting results. Holt and Fisher (1960) found that nitrogen caused deeper rooting of coastal bermudagrass but did not affect total weight of root material.…”
Section: Resultsmentioning
confidence: 92%
“…Production of Underground Plant Material.-Investigations of root production and distribution as influenced by fertilization, indicated varied and conflicting results. Holt and Fisher (1960) found that nitrogen caused deeper rooting of coastal bermudagrass but did not affect total weight of root material.…”
Section: Resultsmentioning
confidence: 92%
“…Reports ofN effects on root distribution are contradictory. While Oswalt et al (1959) report that supplemental N decreased the rooting depth oforchardgrass and bromegrass and caused root proliferation and activity near the soil surface, Holt and Fisher (1960) reported that N fertilization of bermudagrass at rates up to 1400 kg N ha-t had no effect upon the amount of roots at any one depth nor was there any interaction of depth of rooting with N level although there was a trend towards deeper root penetration.…”
Section: Contamination Of the Root Samples Withmentioning
confidence: 98%
“…At the 15‐ to 45‐cm depth, the impact of HM continued to affect root‐rhizome mass of Coastal but not that of common bermudagrass. Root‐rhizome mass of Coastal bermudagrass from nongrazed, small plots showed root‐rhizome mass to exceed 6160 kg ha −1 in the 0‐ to 15‐cm depth (Holt and Fisher, 1960).…”
Section: Resultsmentioning
confidence: 99%